CHARACTERISTIC OF AGARWOOD TEA FROM GYRINOPS VERSTEEGII FRESH AND DRY LEAVES - I Gde Adi Suryawan Wangiyana; Sami'un (JURNAL SANGKAREANG MATARAM, 2018)
Gyrinops versteeegii in Lombok Island mainly be focus on cultivating of agarwood gubal commodity which need up to 14 years for production. Use the leaf to make a tea is one of potential alternative commodity form G. versteegii which give guarantee for agarwood farmers to have a continuous product from their plantation. The purpose of this research is to study different characteristic of tea from fresh and dry agarwood leaves. Leaves sample were taken from the branch near the shoot of G. versteegii tree. After being washed multiple times, 20 gr of fresh leaves were boiled in1 L of 100oC water for 5 minutes. Ten gram of Dry leaves after losing 60% of its water content was brewed in 1 L of 100oC water for 5 minutes. Both fresh leaf tea and dry leaf tea were added with 7,5% w/v sucrose. Fresh leaf tea and Dry leaf tea have a different color, brightness, and turbidity. These 2 types of tea also different in odor and taste. Dry leaf tea has a strong odor and bitter taste while fresh leaf tea has a light odor and weak taste. Slighly bitter taste from dry leaf tea possibly caused by tannin. It could be concluded that agarwood tea from fresh leaf and dry leaf has a different appearance, odor, and taste. Study about phytochemistry of agarwood tea and the hedonic test is needed for better understanding about agarwood tea.